Identification and Characterization of Exopolysaccharides of Staphylococcus epidermis and Staphylococcus capitis Isolated from Goat Gut - Ramachandran, Praveen; Janarthanan, Navitha Thanu; Balakrishnan, Lavanya; Palanisami, Sharba Deepa; Joseph, Sindhya; Dhanaraj, Sharmila Srimathi; Antony, Trisha Mary Pandipilly; Ramasamy, Suganthi (Asian Journal of Biological and Life Sciences, 2020)
The present work was delineated to isolate exopolysaccharide (EPS) producing lactic acid bacteria such as Staphylococcus epidermis and Staphylococcus capitis. The synthesis of exopolysaccharide was identified by growing the cultures in Congo red agar and visual identification of black colonies proved to have EPS production by both the isolates. The exopolysaccharides has been extracted and quantified. The characterisation of exopolysaccharide was done by SEM, EDAX and FTIR. The antioxidant activity of the exopolysaccharides has been performed and the results indicated that there was increasing inhibition with increase in concentration. The metal chelating assay resulted that ferrozine can quantitatively form complexes with Fe2+. Thus EPS shows metal chelating activity. The emulsifying activity of the exopolysaccharides has been performed and the result proves that the EPS can be used as a potent bio emulsifier in food industries. Thus, the results suggested that the exopolysaccharides has potential application in pharmaceutical and food industries.
Keywords: Antioxidant; Emulsification; Exopolysaccharide; Lactic acid bacteria; Metal chelating activity; Staphylococcus